Identifikasi Potensi Wisata di Wilayah Kasepuhan Wewengkon Citorek - Nofiyanti, Fifi; Nasution, Deivy Zulyanti; Pusparani, Pusparani (Jurnal Ilmiah Pariwisata, 2022)
This study aims to determine the tourism potential in the Kasepuhan Wewengkon Citorek area which is located in Lebak Banten. The research method used is qualitative with a descriptive approach. The research was conducted by means of observation, interviews. The results showed that there are 3 (three) criteria for tourism potential: (1) the potential for natural tourist attractions (mountains, rice fields, seas, forests, waterfalls, and plantations. The country above the clouds has become known as a tourist attraction that has become known outside community Currently starting the development of tourist attractions on Mount Kendeng, according to Jaro that Mount Kendeng has more beauty than the land above the clouds; (2) Identification of potential cultural tourism attractions (crafts, historical heritage, local traditions, culinary, festivals) culture, traditional villages, museums, livelihoods, kasepuhan, traditional tools). There are characteristics of cultural potential in the form of seren taun, ngahuma, ngarengkong, playing karinding musical instruments and angklung buhun, straw brooms, pasung tuhur culinary, kaneron bags, straw brooms, headbands, caping hats. rice; (3) Identification of the potential for artificial tourism in Kasepuhan Wewengkon Citorek, there is a strawberry farm made by the community and located not far from the country above the clouds touris. Keywords: Tourism Potential, Wewengkon Citorek